Prospects for the development of the outrigger designs for railway cranes - Khayitbayeva, Г.Б.; Murzagaliev, А.Ж.; Sazambayeva, Б.Т.; Ordabayeva, Г.М.; Kossybayev, Ж.З. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2026)
This article examines the issue of ensuring the stability and operational safety of railway recovery cranes. It demonstrates that one of the key components determining the crane’s stability during loading and transport operations is the outriggers, which absorb the majority of the forces and ensure their redistribution to the supporting surface. The aim of the study is to analyze the design solutions for outriggers of railway lifting cranes and to identify promising directions for their design improvement. Based on a patent analysis of existing technical solutions, a classification of modern outrigger designs has been developed into the following groups: systems designed to reduce unit pressure on the ground; designs differing in configuration and layout; solutions involving the use of modern materials in working elements; systems equipped with devices for monitoring crane stability during operation. Based on the identified classification criteria, a morphological table was created, allowing for the synthesis of possible design variants for outriggers, justifying the direction of further research, and determining the main parameters of the research object. A comparative analysis of existing methods for calculating the stability of railway cranes with outriggers has been carried out. The prospect of increasing the efficiency of the support elements by optimizing their configuration and using modern composite materials is shown.